Family support mediates the relationship between medication adherence and quality of life among patients with hypertension in Ghana: A cross-sectional study - Cynthia Serwaa Akoto Osei; Jacob Solomon Idan; Edmund Baah-Akyeamfour; Bhavana Singh; Daniel Boateng (PLoS ONE, 2026)
Background Hypertension poses significant challenges to quality of life globally. While medication adherence is essential for managing hypertension, psychosocial factors like family support may influence both adherence and quality of life. This study investigated the mediating role of family support in the relationship between medication adherence and quality of life among persons with hypertension in Ghana. Methods A cross-sectional study was conducted among 365 patients with hypertension attending Kwame Nkrumah University of Science and Technology Hospital in Kumasi, Ghana. Data were collected using structured questionnaires, including the Short Form-36 for quality of life assessment, the Family Adaptation, Partnership, Growth, Affection, Resolve scale for family support measurement, and the Morisky Medication Adherence Scale. Mediation analysis was performed using R statistical software. Results Five models with increasing levels of adjustment were constructed for the mediation analysis. Higher medication adherence was significantly associated with better quality of life (Total Effect: (β) = 1.07, 95% CI: 0.63–1.50, p < 0.001). Family support significantly mediated this relationship (Average Causal Mediation Effect = 0.09, 95% CI: 0.02–0.19, p = 0.008), accounting for 8% of the total effect. The direct effect of medication adherence on quality of life remained significant after adjusting for family support (Average Direct Effect = 0.98, 95% CI: 0.52–1.42, p < 0.001). The mediation effect persisted after adjusting for socio-demographic characteristics, knowledge score, healthcare access, and lifestyle factors (mediated proportion: 8.9%, p = 0.038). Patients from highly functional families demonstrated better quality of life with a unit increase in medication adherence score. Conclusion Family support partially mediates the relationship between medication adherence and quality of life of persons with hypertension. Interventions to improve medication adherence and quality of life should incorporate strategies to enhance family support systems. Healthcare providers should consider the complex family dynamics when developing comprehensive management plans for persons with hypertension.